Guy's Stone Score (GSS) Based on Intravenous Pyelogram (IVP) Findings Predicting Upper Pole Access Percutaneous Nephrolithotomy (PCNL) Outcomes - Lojanapiwat B. (2017)
© 2016 Bannakij Lojanapiwat et al. Objective. To predict the success rate and complications following percutaneous nephrolithotomy via the upper pole using the Guy's Stone Score (GSS) based on the findings of a preoperative intravenous pyelogram (IVP). Patients and Methods. Two hundred and twenty-seven renal operations, which were carried out using PCNL via the upper pole, were classified according to the GSS assigned. Any complications were classified according to the Clavien classification. The success rates and incidence of any complications were compared between each GSS. Results. The immediate success rates were 87.50% of GSS1, 71.43% of GSS2, 53.62% of GSS3, and 38.46% of GSS4, P < 0.01. There were statistically significant differences between the groups in stone size, overall immediate success rate, operative time, number of access tracts, and frequency of tubeless PCNL. Major complications (a Clavien score of 3-5) were significantly higher in the cases with a higher GSS. Conclusion. A GSS based on an IVP is a simple and reliable tool in predicting the success rate and possible complications following upper pole access PCNL.